Comparative evaluation of effectiveness of nisin, amoxicillin/clavulanic acid (Augmentin) and chlorhexidine on E. faecalis as an intracanal irrigant: An In-vitro study - Mariyam Khan; Praveen S Samant; Raju Chauhan; Raazia Khan; Shazia Siddiqui; Saraswati Sachan (Wolters Kluwer Medknow Publications, 2023)
Aim: The present study evaluated the antimicrobial efficacy of chlorhexidine gluconate (CHX), Nisin, and Amoxicillin/Clavulanic Acid (Augmentin) as an intracanal irrigant against Enterococcus faecalis (EF). Materials and Methods: Minimum Inhibitory Concentration (MIC) for EF against Nisin and Augmentin was determined by microbroth dilution technique. Time kill cycle (TKC) analysis was done for 0 MIC, ½ MIC, 1 MIC, and 2 MIC at 0 hour, 15 minutes, 30 minutes, and 45 minutes. At the end of each time period, dilutions were pipetted and swabs of agar plates were done. Incubation of agar plates was done at 37C for 24 hours. Colonies formed were counted. Results: The time kill curve analysis of EF for CHX, Nisin, and Augmentin at different concentrations and time periods showed a gradual decline in mean bacterial count between 0 and 45 minutes for CHX; this decline increases with increase in concentrations and time. Whereas in group Nisin, not much decline in bacterial count is noted for ½ MIC concentrations but a signification reduction of P < 0.001 after exposure to Nisin at 1 MIC ant 2 MIC concentrations. Group Augmentin showed not much reduction in bacterial count with increase in concentration and time. Conclusion: From this study, Nisin is found to be a promising agent in eliminating EF in comparison to other irrigants tested. However, the systemic effect of this irrigant, its biocompatibility, allergic potential, and bacterial resistance needs further investigation.